Być żoną i matką – opiekunką domowego ogniska? Rola rodzinna w wyobrażeniach młodych kobiet - Gębuś, Dorota (Instytut Pedagogiki Uniwersytetu Wrocławskiego, 2015)
Gender is a crucial factor which is diversifying social expectations as to the filling of specific social roles. Some social activities are being assigned to the woman, others for the man. Femininity is strongly related to motherhood, masculinity is expressed through the professional and economic status. Especially in Polish society, being a wife, and most of all being a mother who takes care of home and family, gives women a high social prestige. The stereotype of “Polish Mother”, sacrificing for her children, the exemplary housewife is still firmly entrenched within the social consciousness. This can be seen by analyzing the results of researches about the model of the family. Preferences in this regard are slowly moving away from patriarchal relations evolving towards a more egalitarian relationship. More and more people expresses appreciation for the partnership model, in which a woman and a man are involved in the family and professional issues to a similar extent. If we talk about the predominant actual model, that shows real family life in Poland, often the traditional model is practiced (the woman takes care of the family, the man performs the professional role) and thedisproportionately female model (the woman takes care of the family and performs a professional role, the man performs only a professional role).
Keywords: woman; wife; mother; family role; family model